(untitled) (Revista Logos Ciencia & Tecnología, 2020)
According to the 2018 Psychosocial Risk Analysis, carried out by the Police Family Observatory of the Social Welfare Directorate, 2,229 cases of psychosocial risk were detected in the 22 schools, an increase of 50.5% from the previous year, a figure which has been recurring in the institution’s annual reports. Therefore, this study aims to determine the relationship between psychosocial risk and academic performance in adolescents between the ages of 13 and 15 in Bogotá, using the Questionnaire, Q-PAD, for the Evaluation of Problems in Adolescents as a tool for collecting information in order to identify indices of body dissatisfaction, anxiety, depression, substance abuse, interpersonal problems, family problems, uncertainty about the future, psychosocial risk and self-esteem, as well as the academic performance reported by the schools. 650 adolescents from the 8th, 9th and 10th grades of three schools assigned to the National Police in Bogota participated in this non-experimental-correlational quantitative research. The results showed that 9% of the adolescents presented a high index of psychosocial risk. Regarding academic performance, although a correlation with psychosocial risk was evidenced, it was not significant to determine causality; however, it was found that women have a higher psychosocial risk compared to men. Through the Kruskal-Wallis statistical analysis, an association was found between academic performance and family types, since members of nuclear families show better academic performance than those belonging to extended families. Finally, with the descriptive statistic, it was identified that the family typology presents a significant correlation with the psychosocial risk, indicating that students which come from extended families have a lower risk than those who belong to recomposed families.